2019
DOI: 10.1007/s00268-019-04931-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathology Evaluation of Reduction Mammaplasty Specimens and Subsequent Diagnosis of Malignant Breast Disease: A Claims‐Based Analysis

Abstract: Background This study aimed to measure the use of pathology evaluation of breast specimens among patients undergoing reduction mammaplasty and assess rates of new diagnoses of breast disease and associated cost. Methods We analyzed the Truven MarketScan Databases from 2009 to 2015 to identify adult female patients undergoing reduction mammaplasty for macromastia. We recorded patient age, rates of obtaining pathology evaluation, new diagnoses of benign or malignant breast disease after pathology evaluation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 44 publications
1
11
1
Order By: Relevance
“…The cancer rate in patients with no history of breast cancer in previous studies ranged from 0 to 1% 12–26 . Similar to those studies, the cancer rate in our study was 0.36%.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The cancer rate in patients with no history of breast cancer in previous studies ranged from 0 to 1% 12–26 . Similar to those studies, the cancer rate in our study was 0.36%.…”
Section: Discussionsupporting
confidence: 89%
“…in 2012 suggested gross‐only evaluation for patients aged <30 years 11,26 . However, previous studies, including ours, reported many cancer cases in patients aged between 30 and 35 years 5,19,23–25 . In our study, we did not observe any cancer cases in patients aged <30 years.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations